2005
DOI: 10.1002/biof.5520250117
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 is increased in placenta and cord blood during preeclampsia

Abstract: Preeclampsia is a common (approximately 7% of all pregnancies) disorder of pregnancy in which the normal hemodynamic response to pregnancy is compromised. Despite many years of intensive research, the pathogenesis of preeclampsia is still not fully understood. The objective of the present study was to investigate the levels of coenzyme Q(10) (CoQ(10)) in placental tissue compared to maternal and umbilical cord levels both during normal pregnancy and in those complicated with preeclampsia. Pregnant women (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…These findings have been confirmed by other cohort studies [10,11]. However, these data were collected from women with established pre-eclampsia and, therefore, it was not possible to determine whether the biochemical changes were a cause or a consequence of pre-eclampsia.…”
Section: Introductionsupporting
confidence: 50%
“…These findings have been confirmed by other cohort studies [10,11]. However, these data were collected from women with established pre-eclampsia and, therefore, it was not possible to determine whether the biochemical changes were a cause or a consequence of pre-eclampsia.…”
Section: Introductionsupporting
confidence: 50%
“…Several potential mechanisms have been proposed for the increase in maternal serum CoQ10 during pregnancy. It is unlikely that this increase in maternal serum CoQ10 was derived from fetus, because previous studies [20, 21] have demonstrated that, during a normal pregnancy, the CoQ10 levels in cord blood are lower than in maternal plasma. However, a comparison of CoQ10 levels between umbilical arterial blood and venous blood is necessary to clarify any discrepancy in the levels of CoQ10 between the fetus and mother.…”
Section: Discussionmentioning
confidence: 97%
“…However, a comparison of CoQ10 levels between umbilical arterial blood and venous blood is necessary to clarify any discrepancy in the levels of CoQ10 between the fetus and mother. In addition, it has been reported that there is a significant decrease in plasma CoQ10 in women with preeclampsia, and that the CoQ10 content in the placenta of these women was significantly increased compared with those of women with normal pregnancies [20]. As a result, there is insufficient proof that CoQ10, which derives from fetoplacental sources, has any effect on increased levels of CoQ10 in the maternal serum.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study showed that levels of coenzyme Q10 in preeclamptic women were half those in women without preeclampsia, which has been confirmed by cohort studies. 64,69,70 The effect of coenzyme Q10 supplementation in pregnant women at increased risk of preeclampsia was recently assessed in a randomized, doubleblind, placebo-controlled trial. Two hundred and thirty-five women were assigned to receive 200 mg of coenzyme Q10 or placebo daily from 20 weeks of pregnancy until delivery ( Table 2).…”
Section: Next Generation Antioxidants For Prenatal Nutrition Coenzymementioning
confidence: 99%